Brothers from afar rabbinic approaches to apostasy and reversion in medieval Europe - Ḳanarfogel, Efrayim 1955- (Wayne State University Press, 2021)
"Revisionist approach to a status of apostates in medieval European rabbinic thought. View this in full screen In Brothers from Afar: Rabbinic Approaches to Apostasy and Reversion in Medieval Europe, Ephraim Kanarfogel challenges a long-held view that those who had apostatized and later returned to the Jewish community in northern medieval Europe were encouraged to resume their places without the need for special ceremony or act that verified their reversion. Kanarfogel's evidence suggests that from the late twelfth century onward, leading rabbinic authorities held that returning apostates had to undergo ritual immersion and other rites of contrition. He also argues that the shift in rabbinic positions during the twelfth and thirteenth centuries was fundamentally a response to changing Christian perceptions of Jews and was not simply an internal halakhic or rabbinic development. Brothers from Afar is divided into seven chapters.
Keywords: Geschichte 1000-1500; Aschkenasim; Rabbinismus; Apostasie; Judentum; Europa; Apostasy / Judaism / History; Judaism / Europe / History; Apostasy / Judaism; History